A Small CO2 Leakage May Induce Seismicity on a Sub‐Seismic Fault in a Good‐Porosity Clastic Saline Aquifer - Stanislav Glubokovskikh; Erdinc Saygin; Serge Shapiro; Boris Gurevich; Roman Isaenkov; David Lumley; Rie Nakata; Julian Drew; Roman Pevzner (Geophysical Research Letters)
Abstract Despite public concerns, only a few CO2 injections into saline aquifers have reported microseismicity. We analyze passive seismic monitoring of a small (15,000 tonnes and 0.15 MPa pressure) injection of supercritical CO2‐rich mixture for Stage 2C of the CO2CRC Otway Project (Victoria, Australia), which induced 19 detectable events with maximum moment magnitude MW‐0.5. The locations and dynamic parameters of the triggered events indicate a reactivation of a small fault patch where CO2 flowed through the fault. Time‐lapse seismic images of the plume and reservoir simulations show that the reactivation occurred when the CO2 plume reached this fault. This might be indicative of a fault weakening by the plume that enabled subsequent reactivation by pressure variations. Our observations suggest that a leakage from a commercial‐scale storage may trigger felt seismicity in the overburden without strong overpressure, thus, the de‐risking workflows should involve a detailed study of small faults.